2018
DOI: 10.21873/cgp.20092
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Pelvic Autonomic Nerve in Nerve-sparing Radical Hysterectomy for Cervical Carcinoma

Abstract: Abstract. Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
2
1
Order By: Relevance
“…Because of the close proximity of the paracervix and supporting tissues around the uterus with the pelvic nerves, the integrity of pelvic innervation may be compromised during RH [22]. Although no significant differences between patients who underwent nerve-sparing procedures and those who underwent non-nerve-sparing procedures were observed in our study, some studies have demonstrated that nerve-sparing techniques appear to improve bladder function without compromising overall survival [23]. Ditto et al [24] reported a significant difference between patients undergoing nerve-sparing RH and patients undergoing non-nerve-sparing RH.…”
Section: Discussioncontrasting
confidence: 54%
“…Because of the close proximity of the paracervix and supporting tissues around the uterus with the pelvic nerves, the integrity of pelvic innervation may be compromised during RH [22]. Although no significant differences between patients who underwent nerve-sparing procedures and those who underwent non-nerve-sparing procedures were observed in our study, some studies have demonstrated that nerve-sparing techniques appear to improve bladder function without compromising overall survival [23]. Ditto et al [24] reported a significant difference between patients undergoing nerve-sparing RH and patients undergoing non-nerve-sparing RH.…”
Section: Discussioncontrasting
confidence: 54%
“…These findings suggest difficulties in identifying the IHP. In a report studying the proteomic analysis of the pelvic autonomic nerve, both soft tissue and vesical branch of the IHP nerve from five women were collected during surgery, and the existence of nerve fiber was not confirmed in one case (20%) 25 . A report determined the nerve area density in cross sections of resected parametria at various distances from the cervix using a point counting technique.…”
Section: Discussionmentioning
confidence: 99%
“…Sympathetic sacral splanchnic nerves from sacral located sympathetic ganglia also send branches into the IHP [9][10][11]. The anterior division of the IHP supplies nerve fibers to the bladder and ureter (i.e., vesical branches of the IHP, also known as vesical branches of the pelvic nerve [12][13][14][15][16], anterior branches of the IHP [9,17,18], and bladder nerve branches [10]). The anterior division of the IHP also supplies nerve branches to the uterus and vagina, or prostate [7]; see [9][10][11] for more regarding the anatomy of this entire plexus.…”
Section: Introductionmentioning
confidence: 99%